Influence of Radiation on Heat and Mass Transfer in MHD Fluid Flow Over an Infinite Vertical Porous Surface with Chemical Reaction - CH. Baby Rani; Sk. Mohiddin Shaw; G. Dharmaiah (International Journal of Mathematics And its Applications, 2017)
An examination is completed to think about the nonlinear MHD stream with heat and mass transfer attributes of an incompressible, viscous, electrically directing and Boussinesq fluid over a vertical moving permeable porous plate in presence of homogeneous chemical reaction of first request and heat radiation impacts. The problem is explained numerically utilizing the perturbation technique for the velocity, the temperature, and the concentration field. The impacts of different thermo-physical parameters on the velocity, temperature and concentration has been processed numerically and discussed about subjectively.